Racial attitudes in America today : one nation, still divided - Peterson, Clarissa (Political science professor); Riley, Emmitt Y., III (New York, NY : Routledge, 2022)
"With this book, Clarissa Peterson and Emmitt Y. Riley, III dive into how racial attitudes change and inform political decisions. Peterson and Riley use racial resentment, black blame, and racial identity to investigate the extent to which racial attitudes influence vote choice, evaluations of Black Lives Matter, and attitudes toward public policies. Moving the conversation beyond the study of Blacks and Whites, the authors unpack the potency of racial attitudes among Asians, Blacks, Hispanics, and Whites. In doing so, they challenge our understanding of how racial attitudes are central to political decision-making in an environment that is inundated with anti-Blackness. The book reframes discussions of racial attitudes to propose that, like white people, some racial minorities in the U.S. harbor negative attitudes toward Black people. The authors suggest that while white political attitudes are significantly explained by racial resentment, the overall influence of racial resentment on political decision-making among some racial groups, may be mitigated by racial identity. At a time when white supremacists walk unhooded in the streets of America, Racial Attitudes in America Today is essential reading for educators wanting to fully engage with and understand racial resentment in America and undergraduate students in the fields of political science, sociology, history, and psychology"--
Boiling racial tensions in the United States of America -- The continued influence of White racial attitudes -- Racial attitudes among Asians and Hispanics : a clash of American and racial identities -- Racial attitudes among Blacks : the links between collective Interest, Black blame, and racial identity -- The consequences of racial attitudes in a fragile democracy.
Keywords: Race -- Political aspects -- United States; United States -- Race relations -- Political aspects; Minorities -- United States -- Attitudes; White people -- United States -- Attitudes; Racism -- United States -- History; Public opinion -- United States; United States -- Race relations -- Public opinion; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Discrimination & Race Relations